PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN EFIKASI DIRI TERHADAP NIAT BERWIRAUSAHA DI KALANGAN MAHASISWA UNIVERSITAS DARUNNAJAH - Engga Jalaludin; Rizka Fajrina S; Nur Majdina (STIE Mahardhika, 2023)
This study intends to perform empirical research on students at Darunnajah University's entrepreneurship education, self-efficacy, and entrepreneurial goals. On the basis of cross-sectional data, the author employs quantitative methodologies. Students at the Darunnajah University's business faculty are the intended audience for the use of random sampling procedures. To get responses from respondents, the author employed a survey questionnaire. The structural equation model (SEM) is employed by the author. The study's findings indicate that the introduction of opportunities and the acquisition of entrepreneurial knowledge, specifically, have a strong positive impact on entrepreneurial self-efficacy and entrepreneurial goals. In addition, the entrepreneurial self-efficacy variable significantly and favourably influences entrepreneurial inclinations.